2009
DOI: 10.1590/s1676-06032009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização das assembléias de peixes de riachos de cabeceira no período chuvoso na bacia do rio Cachoeira (SE da Bahia, NE do Brasil)

Abstract: Visando conhecer a riqueza de espécies e aspectos ecológicos das assembléias ícticas de riachos de cabeceira da Bacia do Rio Cachoeira, foram realizadas coletas de peixes, de variáveis estruturais do ambiente e da água de oito riachos durante o mês de dezembro de 2007. Foram capturados 1.915 indivíduos pertencentes a 19 espécies das quais, cerca da metade, composta por organismos inferiores a 50 mm, o que sugere endemismo. Espécies com "status" taxonômico indefinido podem ser novas para a ciência. A confirmaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
1
5
0
6
Order By: Relevance
“…On the other hand, although highly degraded matrices such as citrus and sugarcane plantations surrounded the river at some points, riparian zone that was composed of arboreal vegetation, favored the occurrence of fish. These results corroborated other studies (Bruschi Junior et al, 2000;Ferreira & Casatti, 2006a;Cetra et al, 2005) that have shown that higher levels of fish diversity are associated with more preserved environments.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, although highly degraded matrices such as citrus and sugarcane plantations surrounded the river at some points, riparian zone that was composed of arboreal vegetation, favored the occurrence of fish. These results corroborated other studies (Bruschi Junior et al, 2000;Ferreira & Casatti, 2006a;Cetra et al, 2005) that have shown that higher levels of fish diversity are associated with more preserved environments.…”
Section: Discussionsupporting
confidence: 92%
“…Foram capturados 1.915 indivíduos pertencentes a cinco ordens, nove famílias e 26 espécies (Cetra et al 2009). Destes, 55 indivíduos foram identificados como Characidium aff.…”
Section: Resultsunclassified
“…Independente do estado de preservação da vegetação ripária, a característica predominante do entorno foi classificada em margem com gramínea e composta por rochas. A porcentagem de cobertura vegetal foi graduada visualmente em quatro níveis: 1) 0 a 25%, 2) 26 a 50%, 3) 51 a 75% e 4) 76 a 100% (Cetra et al 2009).…”
Section: Coleta De Dadosunclassified
See 1 more Smart Citation
“…Recent surveys of freshwater fish in the region resulted in the description of new species, in the identification of endangered species, and the data revealed the presence of endemic species while others had their geographical distribution extended (Cetra and Petrere Jr., 2006;Cetra et al, 2009;Martines-Pinheiro, 2006 a, b). Despite the growing knowledge of the region's richness, it contrasts with information on natural fish populations, such as species, their distribution patterns and their population biology (Cetra et al, 2010).…”
Section: ]Introductionmentioning
confidence: 99%